KONSEP MAHRAM DALAM HUKUM ISLAM ANALISIS HADIS DALAM KITAM AL- MUWATA’ IMAM MALIK - Chaliddin (IAIN LANGSA, 2019)
Mahram in Islamic law is a necessity for women seeking traveler with reachingdistance masafah Qasar, though many occur polimik and debate on the issue, but the Islamic lawexists to balance the life of mankind in general especially those of Muslims. The problem in thispaper is How the concept of mahram according to Islamic law? How intent mahram in the bookof hadith al-Muwata 'Imam Malik? Mahram in Islamic law are those forbidden to marry awoman either nasab, musaharah or rida '(suckling). Mahram in the book of al-Muwata 'ImamMalik are the ones that have been mentioned in the Koran and Hadith dimena they can maintainand preserve women from the threat that the bus makes these women are not at ease, comfortableand peaceful so that if women who travel or other sebaginya unaccompanied by mahramnya thedevil and the devil upon him, the quality of the chains and Matan hadith of Abu Hurairah thathas takhrijed by Imam Malik is Sahih.